The house - Drake, Raelyn (2018)
On a dare, Grace, Kat, and Damien agree to spend an hour in a house rumored to be haunted, and their scientific investigation reveals hidden truths.
Keywords: Haunted houses -- Fiction; Detective and mystery fiction